A dynamic model of commutes - Jan Rouwendal; Arno van der Vlist (European Regional Science Association (ERSA), 2002)
This paper studies the interaction between job mobility and housing mobility by considering the duration of commutes. Conventional models assume that the employment location has priority over the residential location and that the latter is adapted to the former. This implies that the duration of commutes that start with a job change is often short, because of a related house change that follows soon. In the paper we distinguish commutes on the basis of the mobility types that started and ended their existence. The empirical analysis of this paper shows that both job mobility and housing mobility are often followed by repeat-mobility, but also by mobility of the other type. These empirical results refer to a sample of Dutch workers who reported changes on the housing and labor market between 1990 and 1998. In order to capture these empirical findings in a formal model, we specify duration models that focus on the time during which employment-housing arrangements (hence, commutes) remain unchanged. We start with estimating univariate duration models for commutes and proceed to competing risks models. Estimation results for these models confirm that commutes that start with housing mobility and those that start with job mobility have similar characteristics with respect to induced future mobility. Moreover, we find that the commuting distance has a limited effect on job mobility, that there is no evidence for the existence of a critical commuting distance and that workers belonging to dual earner households are more mobile on both markets than others.
Keywords: 330